UNVEILING THE POWER OF FIGURATIVE LANGUAGE IN THE INDONESIAN PRESIDENTIAL CANDIDATES’ COMMUNICATION LANGUAGE, 2024, ON ONLINE ENGLISH NEWS - Anastasia , Happy (LPPM STISIPOL Mujahiddin, 2024)
Figurative language is commonly used in literary works with its purpose to gratify readers/audiences’ imaginative pleasures. However, it also appears in the communication language of Indonesian presidential candidates, 2024. In order to find out what types of figurative, what dominant types are used, and how the figurative works to reveal the candidates’ characterstic personalities, therefore, this study is conducted. This study is qualitative. The data are obtained through 9 news of English online about three Indonesian presidential candidates, 2024. The data are analyzed through: data reduction, data display, and verification. As the results, there are four types of figurative used by the candidates: Metaphor, Personification, Hyperbole, and Irony, in which the total types used by Prabowo: 28 data, Anies: 23 data, and Ganjar: 20 data. While the dominant types exist in each of the candidates’ language: Prabowo: Hyperbole, around 39.29%, Anies: Hyperbole, around 47,83%, and Ganjar: Personification, around 40.00%. As the conclusions, the figurative in the candidates’ language has the power to unveil their characteristics personalities. From the dominant types exist in their communication language, it shows that Hyperbole in Prabowo reveals loyalty and his military attitude as a corp, Hyperbole in Anies reveals his intellectuality and education prioritized, while Personification in Ganjar reveals his spirit of conquering and winning.